Additive Influence of Extracellular pH, Oxygen Tension, and Pressure on Invasiveness and Survival of Human Osteosarcoma Cells - Matsubara, Takao; DiResta, Gene R.; Kakunaga, Shigeki; Li, Dasen; Healey, John H. (Frontiers in Oncology, 2013)
Background/Purpose: The effects of chemical and physical interactions in the microenvironment of solid tumors have not been fully elucidated. We hypothesized that acidosis, hypoxia, and elevated interstitial fluid pressure (eIFP) have additive effects on tumor cell biology and lead to more aggressive behavior during tumor progression. We investigated this phenomenon using three human osteosarcoma (OS) cell lines and a novel in vitro cell culture apparatus. Materials and Methods: U2OS, SaOS, and MG63 cell lines were cultured in media adjusted to various pH levels, oxygen tension (hypoxia 2% O2, normoxia 20% O2), and hydrostatic gage pressure (0 or 50 mmHg). Growth rate, apoptosis, cell cycle parameters, and expression of mRNA for proteins associated with invasiveness and tumor microenvironment (CA IX, VEGF-A, HIF-1A, MMP-9, and TIMP-2) were analyzed. Levels of CA IX, HIF-1α, and MMP-9 were measured using immunofluorescence. The effect of pH on invasiveness was evaluated in a Matrigel chamber assay. Results: Within the acidic–hypoxic–pressurized conditions that simulate the microenvironment at a tumor’s center, invasive genes were upregulated, but the cell cycle was downregulated. The combined influence of acidosis, hypoxia, and IFP promoted invasiveness and angiogenesis to a greater extent than did pH, pO2, or eIFP individually. Significant cell death after brief exposure to acidic conditions occurred in each cell line during acclimation to acidic media, while prolonged exposure to acidic media resulted in reduced cell death. Furthermore, 48-h exposure to acidic conditions promoted tumor invasiveness in the Matrigel assay. Conclusion: Our findings demonstrate that tumor microenvironmental parameters – particularly pH, pO2, and eIFP – additively influence tumor proliferation, invasion, metabolism, and viability to enhance cell survival and must be controlled in OS research.